Exploring the role of the Recovery College model as a transformative tool for recovery-oriented practice: perceived benefits and perspectives from health practitioners in Quebec, Canada - Bellemare, Julie; Vallée, Catherine; Briand, Catherine; Sauvageau, Anick; Drolet, Marie-Josée (Frontiers in Psychiatry, 2024)
Mental health practitioners (MHPs), including occupational therapists (OTs), need support to adopt a truly recovery-oriented practice. Like other practitioners, if OTs often embrace the principles of recovery as a philosophical foundation for their practice, these principles may not always reflect in their attitudes, behaviors or in their interventions. While further research is needed to demonstrate the positive effects of recovery-oriented training programs on MHPs' attitudes and practice, there is a need to explore novel training programs. The Recovery College (RC) model is one of the interventions that are designed to facilitate these changes in practice, through co-production and co-delivery of recovery-focused courses curriculum. Although the perceived benefits and outcomes of RC courses are widely documented, very few studies focus specifically on what MHPs gain from them or on their global experience. The aim of this article is to describe the experience of MHPs learners in RC courses and the perceived benefits on their practice. Methods: An exploratory descriptive qualitative study was conducted. Data were collected through semi-structured interviews and analyzed using Miles and Huberman’s stepwise qualitative analysis method. Results: Participants were 13 MHPs working in community organizations or healthcare institutions and who participated as learners in a RC, in the province of Quebec, Canada. Ten themes emerged from the qualitative analysis. Participants expressed their perspectives on the format of the courses, their initial expectations and their recommendations. They also identified the types of knowledge they shared during the courses. Participants reported changes in their practice, raised awareness on their clinical and personal issues, improved well-being and recovery. Group composition, interactions within the group, complementarity of the different types of knowledge, and pedagogical design and learning activities were identified as key ingredients of RC. Conclusions: This study highlighted RCs' role in enriching MHPs clinically and personally. RC curriculum and courses drive changes in practice and attitudes towards service users. RCs may assist MHPs reflect on practice and improve their clinical reasoning. This study advances understanding of a promising, accessible training program for adopting a recovery-oriented practice amid a paradigm shift among MHPs and OTs.